The vampire diaries. The eighth and final season - Dobrev, Nina, 1989-; Wesley, Paul, 1982-; Somerhalder, Ian, 1978-; McQueen, Steven R., 1988-; Graham, Katerina, 1989-; Accola, Candice, 1987-; Smith, L. J. (Lisa J.); Warner Bros. Entertainment; Warner Home Video (Firm); Warner Bros. Television ([Place of publication not identified] : [Publisher not identified], 2016)
Sink your teeth into the Vampire Diaries' final chapter and prepare to say goodbye to this beloved series. Season eight begins with Damon and Enzo continuing on their killing spree, both following the commands of a sinister and unnatural force. While Bonnie, Stefan and Caroline are grieving their loss, they team up to investigate who or what may be the cause of their disappearance. Alaric joins the search and to look for clues on how they escaped the Armory vault and Matt's family history will reveal a deeper connection to Mystic Falls and how he may be able to save the town from destruction. The final season promises high stakes romance and drama in all 16 thrilling episodes of television's most addictive and captivating vampires.
Disc 1. Disc 2. Disc 3.
Title from container.
Based upon the book by L.J. Smith.
DVD release of episodes originally broadcast on television in 2013-2014.
Special features: 4 all-new featurettes ; gag reel ; unaired scenes.
Nina Dobrev, Paul Wesley, Ian Somerhalder, Michael Trevino, Steven R. McQueen, Kat Graham, Candice Accola, Zach Roerig.
MPAA rating: Not rated.
Keywords: College students -- Drama; Vampires -- Drama; Brothers and sisters -- Drama; Man-woman relationships -- Drama; Television series; Vampire television programs; Fantasy television programs; Fiction television programs; Video recordings for the hearing impaired